Regulation of nuisance telemarketing calls and text messages (telephone spam) in Nigeria: lessons from the US and the UK (2017)
Telephone spam is a common problem in the telecommunications sectors of most countries, and Nigeria is not an exception. The developed countries like the United States of America and the United Kingdom have adopted different approaches, including legal and regulatory, which are in no small measure productive in regulating telephone spamming. The Nigerian regulation of telephone spam is not with the required seriousness, therefore is at low ebb compared to U.S. and U.K.